2015
DOI: 10.1152/jn.00809.2014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of artificial whisking related signals in barrel cortex

Abstract: Rats use rhythmic whisker movements, called active whisking, to sense the environment, which include whisker protractions followed by retractions at various frequencies. Using a proxy of active whisking in anesthetized rats, called artificial whisking, which is induced by electrically stimulating the facial motor nerve, we characterized the neural responses evoked in the barrel cortex by whisking in air (without contact) and on a surface (with contact). Neural responses were compared between distinct network s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Although this preparation resembles in some respects anesthetized conditions where the whiskers are made to move artificially by electrical stimulation of the facial motor nerves (Brown and Waite, 1974; Castro-Alamancos and Bezdudnaya, 2015; Szwed et al, 2003), all of our data were collected in the awake, alert state. Since several studies have highlighted how brain state and the level of alertness can dramatically influence sensory processing and the firing of specific cortical subtypes (Adesnik et al, 2012; Castro-Alamancos, 2004a, b; Castro-Alamancos and Oldford, 2002; Greenberg et al, 2008; Lee et al, 2013; Niell and Stryker, 2010; Poulet and Petersen, 2008; Reimer et al, 2014; Vinck et al, 2015), we consider it essential that we performed all of our experiments in the awake state while mice ran and whisked of their own volition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this preparation resembles in some respects anesthetized conditions where the whiskers are made to move artificially by electrical stimulation of the facial motor nerves (Brown and Waite, 1974; Castro-Alamancos and Bezdudnaya, 2015; Szwed et al, 2003), all of our data were collected in the awake, alert state. Since several studies have highlighted how brain state and the level of alertness can dramatically influence sensory processing and the firing of specific cortical subtypes (Adesnik et al, 2012; Castro-Alamancos, 2004a, b; Castro-Alamancos and Oldford, 2002; Greenberg et al, 2008; Lee et al, 2013; Niell and Stryker, 2010; Poulet and Petersen, 2008; Reimer et al, 2014; Vinck et al, 2015), we consider it essential that we performed all of our experiments in the awake state while mice ran and whisked of their own volition.…”
Section: Discussionmentioning
confidence: 99%
“…Yet nearly all these investigations have utilized passive whisker stimulation, which can only probe receptive fields in discretized whisker space, and not in the continuous space scanned by the whiskers. An artificial whisking paradigm in anesthetized animals has allowed investigators to probe spatial coding during active touch, albeit in a reduced brain state (Brown and Waite, 1974; Castro-Alamancos and Bezdudnaya, 2015; Szwed et al, 2003; Wallach et al, 2016; Yu et al, 2015). These studies have revealed how spatial summation and the vibrissotopic map evolve across the sensory hierarchy or change dynamically with experience (Feldman and Brecht, 2005; Fox, 2002; Oberlaender et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in head-fixed mice BF ChAT neurons are also activated by licking (Figure 4 ) and whisking (Eggermann et al, 2014 ), and electrophysiological recordings in primates showed increased spiking of BF neurons during arm movements (Wilson and Rolls, 1990b ). Thus, BF cholinergic neurons may be excited during a broad range of facial and limb movements and as such contribute to cortical activation associated with these movements (Poulet and Petersen, 2008 ; Eggermann et al, 2014 ; Castro-Alamancos and Bezdudnaya, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum amplitude of optogenetically evoked protractions that we found was 11.4 degrees on average in four mice (largest individual mouse average, 14.8 degrees, Figure 2 ; see also Figure 1—figure supplement 1 for single trial examples from multiple tracked whiskers), while studies using artificial whisking in rats report amplitudes of up to 20 degrees ( Yu et al, 2006 ; Castro-Alamancos and Bezdudnaya, 2015 ). One possible explanation is that the excitation light was restricted to a 2–3 mm diameter spot on the whisker pad, while nerve stimulation evokes widespread muscle activation via acetylcholine release throughout the whisker pad.…”
Section: Discussionmentioning
confidence: 74%
“…We also note that optogenetically evoked protractions showed stronger frequency adaptation than reported for artificial whisking. We found strong adaptation over a stimulus frequency range of 2 to 28 Hz ( Figure 2D ), whereas 100 Hz electrical nerve stimulation (artificial whisking) results in sustained whisker protraction for up to 1 s ( Castro-Alamancos and Bezdudnaya, 2015 ). This could be explained by potential differences in muscle groups recruited by optogenetic stimulation in Emx1-Cre;Ai27D mice compared to artificial whisking.…”
Section: Discussionmentioning
confidence: 86%